Contemporary management techniques for excellence in public governance - Mohnot, S.R. (2006)
Indian bureaucracy possesses a robust framework of political administrative system and a treasure of talent. It has often been misguided and mis-handled by the political system. The public governance has developed innate weaknesses by conforming to the loose political system. These seemingly unavoidable compulsions have developed into a structural weakness. The abberations are cascading in their impact and the pervasive corruption is the direct fallout of these abberations. The article identifies some pragmatic suggestions even in the present milieu and advocates adoption of management techniques that can provide proper ambience for the bureaucracy to live upto their potential and expectations. - Reproduced.
Keywords: Public administration - India; Bureaucracy - India; Civil service - India; Civil service